Comparative overview of different fish feed industries in Noakhali region of Bangladesh - Khatun, Sabiha; Rahman, Md Mofizur; Sarkar, Chayan Chandra (Asian Journal of Medical and Biological Research, 2018)
Aqua feeds have been considered as a major subsector in aquaculture. About 25 commercial fish feed industries in Bangladesh are now formulating over 1 million tones of commercial pelleted feed for the use by aquaculture farmers. A survey of different fish feed industries, their produced feed, used raw materials, machineries, distribution and marketing channel was carried out in 2015 at Noakhali of Bangladesh. Four fish feed industries were found having legal permission to produce fish feed in Noakhali. These were Globe-agro vet Ltd, Partex agro fish feed Ltd, Setu feed mills and R.P (Rasulpur) fish feed Ltd with an area of 9, 3, 2 and 3.5 acre, respectively. They used different types of machineries. Maximum machineries were found in Globe-agro vet Ltd. They used 19 types of raw materials where some were local and some were imported. Maximum raw materials were found in Globe-agro vet Ltd and they used 16 types of raw materials. Four types of fish feed were being produced in four fish feed industries and these are nursery, starter, grower, finisher. Square company was common of different raw materials supplier. Feed companies were linked with other business and take loan from local NGO and foreign organization. Their production capacity was not same rate all round the year. They like to produce feed from March to October. There was not so far difference in proximate composition of surveyed feed industries. Protein ranged at 28-35%, Lipid 5-8 %, moisture 10-12 % and Ash 12-18 %. The government should move forward with financial as well as technical support for the expansion and modernization of fish feed industries with a view to protecting the nature from incursive pollutants generated during feed manufacturing process. Asian J. Med. Biol. Res. December 2017, 3(4): 488-493